Assemblages of nocturnal birds in oil palm smallholdings in Selangor, Malaysia - Yahya, Muhammad Syafiq (2017)
Over the last several decades, a large tract of forests in the tropics had been converted into oil palm cultivations (either plantations or smallholdings). The expansion of such cultivation is recognized as one of the major causes of a rapid decline in fauna biodiversity in the tropics. In contrast to large-scale plantations, oil palm smallholdings may support greater levels of biodiversity through the implementation of intercropping practices. To date, the assemblages of nocturnal birds and their response toward environmental factors in oil palm smallholdings still remain unclear. Hence, this study estimated the density of nocturnal bird species as well as examined the effects of local-level and landscape-level variables on the composition of nocturnal bird species in oil palm smallholdings in Peninsular Malaysia. A total of 1,408 individuals of 11 nocturnal bird species (i.e. nine owl and two nightjar species) were recorded from 90 sampling points spaced more than 800 m apart. The density of Spotted Wood Owl (Strix seloputo) was seven individuals per 100 ha, followed by Sunda Scops Owl (Otus lempiji) with 15 individuals for every 100 ha, Common Barn Owl (Tyto alba) with five individuals per 100 ha and Large-tailed Nightjar (Caprimulgus macrurus) with seven to eight individuals for every 10 ha. Biota and/or Environment Matching Analyses (BEST) indicated four predictor variables, i.e. three local variables (crop richness, widths of roads and trenches) and one landscape variables (distance to the nearest road) significantly influenced the community assemblages of nocturnal bird species in the smallholdings. Generalized Linear Models (GLMs) indicated seven predictor variables (i.e. four local variables; height of oil palms, number of oil palms, width of the roads and trenches, and three landscape variables; number of settlements per 100 meter radius, distance to the nearest forest and settlement) significantly influenced the abundances of certain nocturnal species. this study demonstrated that the composition and abundance of nocturnal birds in oil palm smallholdings were influenced by both local and landscape-level variables. This not only improved our understanding on habitat preference of the little known nocturnal birds in Malaysia but also supports that habitat complexity in cultivated areas may aid in biodiversity conservation, at least for nocturnal birds.